Beneficial effects of anthocyanins from red cabbage (Brassica oleracea L. var. capitata L.) administration to prevent irinotecan-induced mucositis. (May 2017) - Tong, Tao; Niu, Yun-Hui; Yue, Yuan; Wu, Shuang-chan; Ding, Hong
Highlights: Anthocyanins (ACs) from red cabbage inhibited Irinotecan-induced mucositis in mice. ACs protected the integrity of epithelial cells in vivo and in vitro . ACs regulated autophagy through suppressing the mTOR pathway. Abstract: Intestinal mucositis is a common side effect of Irinotecan (CPT-11). Anthocyanins (ACs) from red cabbage against CPT-11-induced mucositis were studied. Mice were given CPT-11 (75 mg/kg, i.p. for 4 days) and treated with ACs (50, 100 mg/kg, i.g. for 7 days). On day 8, diarrhea and leukocyte count in blood were assessed. Samples of intestine were obtained for morphometric analysis, myeloperoxidase (MPO), TBARS and GSH assay. The effects of ACs on cytoprotection and intestinal permeability were studied in Caco-2 cells. ACs effectively reversed the signs of intestinal injury, including MPO activity, length of ileum and colon, leukopenia, intestinal architecture, and quantity of ileum mucus. In vitro, pretreatment with ACs enhanced transepithelial electrical resistance (TER) and the expression of ZO-1. Furthermore, the protective effects of ACs were associated to modulate autophagy through mTOR pathway. In conclusion, ACs from red cabbage are candidate for supplementary therapy of CPT-11-induced mucositis.